Research on Modernization Issues and Countermeasures of Company Governance in Company B - Wu, Wanying (International Journal of Global Economics and Management, 2024)
Good corporate governance is a key factor for a company's growth and success, and promoting modernization of corporate governance is an important guarantee for sustainable development. However, family businesses have many complex issues in the process of modernizing corporate governance due to their own characteristics. Paying attention to the governance model of family businesses is of great significance for their future development. This article provides a multi-dimensional analysis of the basic situation of Company B's corporate governance, explores the governance issues existing in the family business, and proposes countermeasures and suggestions. The aim is to provide useful reference and inspiration for other family businesses in terms of corporate governance, thus promoting the sustainable and healthy development of family businesses.